A Pharmacokinetic Interaction Study of Sorafenib and Iced Teas in Rats Using UPLC-MS/MS: An Illustration of Beverage-Drug Interaction. (28th November 2019) - Maher, Hadir M.; Almomen, Aliyah; Alzoman, Nourah Z.; Shehata, Shereen M.; Al-Subaie, Amal
Abstract : Iced teas (ITs), also known as ready-to-drink teas, have gained much popularity among many nations. The modulatory effect of tea beverages on CYP3A4 increases the possibility of their potential interactions with many coadministered medications. Being a substrate of CYP3A4, sorafenib (SOR), the first-line therapy for the treatment of hepatocellular carcinoma, shows a great probability to exhibit pharmacokinetic (PK) interaction with ITs. For this purpose, different groups of Wistar rats were given oral doses of SOR (40 mg/kg), along with different types of ITs. The concentration of SOR in rat plasma was determined using UPLC-MS/MS. Chromatographic analysis was performed on a C18 analytical column, Acquity UPLC BEH™ (100 × 1.0 mm, i.d., 1.7  μ m particle size), using erlotinib (ERL) as an internal standard. Isocratic elution was performed with a mobile phase consisting of two solvents: solvent A (water with 0.1% formic acid) and solvent B (acetonitrile with 0.1% formic acid), in a ratio of 30 : 70, v/v, respectively. Quantitation was performed using MRM of the transitions from protonated precursor ions [M+H] + to product ions at m/z 465.12 > 252.02 (SOR) and m/z 394.29 > 278.19 (ERL). The method was fully validated as per the FDA guidance for bioanalytical method validation in the concentration range of 2.5–500 ng/mL. Different PK parameters were calculated for SOR in all rat groups and groups administered with ITs and SOR, compared with groups with simply water and SOR. Experimental data revealed that ITs caused a general reduction in SOR bioavailability; an approximate reduction of 30% was recorded for all types of tested ITs. These data indicate that ITs could affect the PK profile of SOR in rats.